2020
DOI: 10.1108/ijlm-02-2020-0091
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian logistics practitioners' perceptions on sustainability: an exploratory study

Abstract: PurposeConfronting globalization, logistics systems need to achieve greater efficiency in processes to be competitive. Competitiveness is not related only to economic aspects; companies need to perform their activities aligned to the triple bottom line concept. In this context, the main objective of this research is to analyze how Brazilian professionals think about sustainable logistics through an exploratory study.Design/methodology/approachA set of 33 indicators, compiled from a literature review, was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 86 publications
(161 reference statements)
0
16
1
1
Order By: Relevance
“…By investigating the relative importance of these three dimensions of sustainability, this study makes important theoretical contributions to the field of supply chain management. Contrary to previous studies that suggested that supply chain practitioners give importance to only one or two dimensions of sustainability, considering the social indicators of sustainability in logistics as secondary, [25] the findings reported in this study suggest that all three dimensions of sustainability (environmental, social, and economic) are perceived as equally important by the majority of supply chain practitioners when it comes to the implementation of green supply chain practices. These findings are in line with the findings of another study, which concludes that the firm's environmental, social, and economic aspects need to be considered by the firm when reengineering or designing sustainable supply chain operations and improved decision-making and business performance [30,36].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…By investigating the relative importance of these three dimensions of sustainability, this study makes important theoretical contributions to the field of supply chain management. Contrary to previous studies that suggested that supply chain practitioners give importance to only one or two dimensions of sustainability, considering the social indicators of sustainability in logistics as secondary, [25] the findings reported in this study suggest that all three dimensions of sustainability (environmental, social, and economic) are perceived as equally important by the majority of supply chain practitioners when it comes to the implementation of green supply chain practices. These findings are in line with the findings of another study, which concludes that the firm's environmental, social, and economic aspects need to be considered by the firm when reengineering or designing sustainable supply chain operations and improved decision-making and business performance [30,36].…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in line with the results of research and that show that environmental sustainability indicators are directly related to the economic objectives. To achieve sustainable targets in the supply chain, it is also important to identify a correlation between the sustainability indicators of the supply chain [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature reviews have provided comprehensive insights into sustainable logistics planning (Brandenburg et al 2014;Qaiser et al 2017), green and sustainable logistics practices (Ren et al 2020;Dey et al 2011;Martins et al 2020), sustainable freight transport (Nenni et al 2019;Álvarez and de la Calle 2011), and knowledge management in sustainable logistics (Evangelista and Durst 2015). To improve the intelligence, agility, and efficiency of logistics activities, recent studies have put predominant emphasis on the adoption of new technologies, e.g., big data analytics (Chalmeta and Santos-deLeón 2020), blockchain (Reddy et al 2021), artificial intelligence (AI) (Riahi et al 2021;Tirkolaee et al 2021), internet of things (IoT) (Tijan et al 2019), and additive manufacturing (AM) (Khorram Niaki and Nonino 2017).…”
Section: Introductionmentioning
confidence: 99%